THE EFFECT OF TEMPORAL CONJUNCTION MASTERY AND STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT OF THE 2017/2018 ELEVENTH YEAR STUDENTS OF SMA SWASTA PERSIAPAN STABAT - Ayu Indari - (STKIP Budidaya Binjai, 2019)
The objective of this study was to find out the effect of temporal conjunction mastery and students’ achievement in writing procedure text of the 2017/2018 eleventh year students of SMA Swasta Persiapan Stabat were divided into two classes. They were XI IPA1and XI IPA2. There are 60 students. That number then became the sample of this research. The design of the study was categorized as an experiment quantitative research. It meant there were two groups. They were experimental group that received treatment. This study was conducted by an experimental research. It aimed to measure the students’ ability on descriptive writing. Writing is one of four basic skills. And it is one productive skill in English. It is very important in studying English. The writers used the written test. The writers, as the learning input in understanding the nature of procedure text and the ways to teach procedure text for Senior High School Students effectively and efficiently. The data were acquired by using written test. The test consisted of two types; they were pre-test and post-test. After analyzing the data, the finding indicates that result of analysis was 3.50. It was found out that observed was higher than t-table or it can be said (3.50 > 2.002;α=0.05). It means that temporal conjunction mastery and students’ achievement in writing procedure text of the 2017/2018 eleventh year students of SMA Swasta Persiapan Stabat.